Developing Innovators: A Longitudinal Analysis Over Four College Years - Selznick, Benjamin S.; Mayhew, Matthew J.; Winkler, Christa E.; McChesney, Eric T. (Frontiers in Education, 2022)
The purpose of this study is to examine the influence of collegiate environments and experiences on students’ development of innovation capacities over four years of college. Drawing on an interdisciplinary theoretical framework and reliable innovation measures, students from nine postsecondary institutions in North America were surveyed at three time points: first-year fall, first-year spring, and fourth-year spring. Data were comprehensively analyzed using a growth mixture modeling approach. Results suggest that being a transfer student and having sustained engagement with experiences that connect in-class and out-of-class learning were associated with a robust innovation growth trajectory over-and-above known covariates, including personality traits. Implications for research, theory, and practice are considered.